Tumpuan Harapan Petani di Utara Bumi Lamadukelleng 1992-2015 - Rahmat, Andika; Ahmadin, Ahmadin; Patahuddin, Patahuddin (PATTINGALLOANG, 2017)
This paper discusses the background of Awo Weir construction and how it impact the exictence of Awo Weir for people who have used their water for agriculture. The results of this study indicate that the background of Awo weir construction can not be separated from the Repelita program in the New Order era. Awo weir was built in 1992-1994 and inaugurated by the President of the Republic of Indonesia, Soeharto. Subsequently in its development after the functioning of Awo I (1994), Awo II (1998) and Awo III (2000) have irrigated 5,250 ha of land consisting of potential land and productive land (rice field) until 2015 Awo Irrigation service area of more than 4000 ha of land rice fields located in two districts namely Keera and Pitumpanua. The existence of Awo weir has a impact on the people who have used the irrigation water. The most perceivedÂ  impact of society that is increasing the economic aspect because agriculture is implemented twice a year, which of certainly increases the productivity of agricultural products. This research method is using qualitative.Â  Consisting fo heuristic, kritism, intrepretation and historiography. The data obtained by doing an interview with Head Office of the UPTD Awo Weir, civil servanst irrigation, rectires, farmers and archive (documents from the UPTD) and literature related (books, paper).